Preptin Hormone in Patients with Type 2 Diabetes Induced After Infection with Coronavirus (Covid-19) - Al-Helaly, Luay; M. Mahmood, Zahraa (Scientific Journal for Faculty of Science-Sirte University, 2023)
The research included a study of the levels of the hormone preptin and some biochemical variables in the blood serum of people with type 2 diabetes (T2D) induced after infection with coronavirus (Covid-19). Those variables included: glucose, cholesterol, triglycerides, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) and measurement of levels of antioxidants (Albumin, uric acid, fucose, and glutathione), as well as levels of oxidants compounds: Malondialdehyde and peroxynitrite in Mosul city on (16) a sample for patients and (40) samples for the control group, whose ages ranged between (35-70) years. The results showed that there was a significant increase in the levels of the preptin hormone, glucose, cholesterol and LDL, Beside of decrease in HDL, among T2D patients induced after corona compared with the control group. No significant difference was observed in the TG, HDL, and uric acid between the patients group and the control group. The results indicated that there was a state of high oxidative stress through low levels of antioxidants for glutathione, albumin, and fucose, and a significant increase in the levels of malondialdehyde and peroxynitrite in people with diabetes mellitus developed after corona compared with the control group. The study concluded that the hormone preptin is a good indicator that reflects the status of T2D patients who developed after infection with corona, by comparing them with the levels of antioxidants and oxidants, as well as the levels of fucose and glucose.